Mauritius : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2013)
The article reviews Mauritius' developments and its macroeconomic policies for the imminent years. Growth has been flexible in these years but the postglobal crisis period did not show any remarkable developments. The country was heavily dependent on European exports and vulnerable to external shocks. To undergo debt and external sustainability in 2014-15, the authorities are reframing fiscal and monetary policies, restructuring physical infrastructure policies, and pension and labor reforms. The control of excess of liquidity and improvement in national savings will pave the way to reduce inflation pressures and external imbalances.